Development and Implementation of the Guiding Stars Nutrition Guidance Program - Fischer, Leslie M.; Sutherland, Lisa A.; Kaley, Lori A.; Fox, Tracy A.; Hasler, Clare M.; Nobel, Jeremy; Kantor, Mark A.; Blumberg, Jeffrey (American journal of health promotion, 2011)
Purpose. To describe the collaborative process between a grocery retailer and a panel of nutrition experts used to develop a nutrition guidance system (Guiding Stars) that evaluates the nutrient profile of all edible products in the supermarket, and to report the results of the food and beverage ratings. Design. A collaboration between a private retailer and members of the scientific community that led to the development of a scoring algorithm used to evaluate the nutritional quality of foods and beverages. Setting/Subjects. Northeast supermarkets (n = 160). Measures. Food and beverage nutrition ratings and distribution of stars across different grocery categories. Analysis. Descriptive statistics for rating distributions were computed. T-tests were conducted to assess differences in mean nutrient values between foods with zero versus three stars or a dichotomized variable representing all foods with one to three stars. Results. All edible grocery items (n = 27,466) were evaluated, with 23.6% earning at least one star. Items receiving at least one star had lower mean levels of sodium, saturated fat, and sugars and higher amounts of fiber than products not earning stars. Conclusion. The Guiding Stars system rates edible products without regard to brand or manufacturer, and provides consumers with a simple tool to quickly identify more nutritious choices while shopping. The low percentage of products qualifying for stars reflects poorly on the food choices available to Americans.